2016
DOI: 10.1038/srep27485
|View full text |Cite
|
Sign up to set email alerts
|

CdGAP/ARHGAP31, a Cdc42/Rac1 GTPase regulator, is critical for vascular development and VEGF-mediated angiogenesis

Abstract: Mutations in the CdGAP/ARHGAP31 gene, which encodes a GTPase-activating protein for Rac1 and Cdc42, have been reported causative in the Adams-Oliver developmental syndrome often associated with vascular defects. However, despite its abundant expression in endothelial cells, CdGAP function in the vasculature remains unknown. Here, we show that vascular development is impaired in CdGAP-deficient mouse embryos at E15.5. This is associated with superficial vessel defects and subcutaneous edema, resulting in 44% em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 61 publications
(93 reference statements)
3
18
0
Order By: Relevance
“…It has been reported that IL-8 promotes endothelial cell migration by increasing the activity of Rac1 [22]. Caron et al have shown that activation of Rac1 mediates VEGF-stimulated endothelial cell migration [41]. Our results found that when Rac1 activation was blocked, autocrine VEGF and IL-8-stimulated cell migration was dramatically diminished.…”
Section: Discussionsupporting
confidence: 61%
“…It has been reported that IL-8 promotes endothelial cell migration by increasing the activity of Rac1 [22]. Caron et al have shown that activation of Rac1 mediates VEGF-stimulated endothelial cell migration [41]. Our results found that when Rac1 activation was blocked, autocrine VEGF and IL-8-stimulated cell migration was dramatically diminished.…”
Section: Discussionsupporting
confidence: 61%
“…[20,22] More recently, analysis of a knock-out mouse model has highlighted a critical role for Arhgap31 in vascular development and VEGF-mediated angiogenesis, providing a novel molecular link between Rho GTPase dysregulation and vascular development in this disorder. [23] These findings further support the hypothesis that AOS represents a constellation of clinical features resulting from an early embryonic vascular abnormality. [24] ARHGAP31 mutant transcripts are stable and have been demonstrated to lead to constitutive inactivation of Cdc42 through a gain-of-function mechanism, potentially due to protein truncation impeding regulation of the RhoGAP domain.…”
Section: Rho Gtpase Dysregulationsupporting
confidence: 71%
“…The most important window, BTA1: 64788160-64867718 bp, contributed to 3.44% of the genetic variance of 18MW and was located within gene Rho GTPase activating protein 31 (ARHGAP31). ARHGAP31 encodes a GTPase-activating protein (GAP) and plays a role in regulating the cellular processes of cycling between an inactive GDP-bound and active GTP-bound conformation [36]. GAP has been reported to have functions in protein trafficking and cell growth and serves as a molecular switch involved in the regulation of various cytoskeleton-related events and gene transcription [37].…”
Section: Wssgwas For Yw and Byadgmentioning
confidence: 99%